Speech Disorders in Deaf People - Pratiwi, Ditha Ananda; Saputra, Tri Endar Yogi Setiadi (Pustaka Digital Indonesia, 2024)
Speech impairment in deaf people is a complex challenge in the context of learning and communication development. This study aims to determine speech production by deaf people. This research used a qualitative approach with the subject of the research is a single subject aged 50 years. Data was collected through interviews with the family of the deaf person and observation of a single subject aged 50 years who also had a speech disorder and mental health problems. This research shows that there is one statement from the respondent said that “she sometimes gets frustrated and angry when what she wants to say cannot be conveyed properly, which disturbs her mental health”. That is one of the main causes so that they can be mental health. Therefore further research is needed to understand more about speech impairment in deaf people and to develop more effective intervention strategies. By combining these findings, we can gain a better understanding of the complexities of speech impairment in deaf people and formulate recommendations for clinical practice and future research.